STAT3 governs hyporesponsiveness and granzyme B‐dependent suppressive capacity in human CD4+ T cells. Issue 3 (14th November 2014) - Schmetterer, Klaus G.; Neunkirchner, Alina; Wojta‐Stremayr, Daniela; Leitner, Judith; Steinberger, Peter; Pickl, Winfried F.
Abstract : Signal transducer and activator of transcription 3 (STAT3) integrates key signals of cell surface immune receptors, yet its precise role in cluster of differentiation (CD)4 + T cells is not well‐established. Current research has indicated T‐helper cell 17–inducing roles but also tolerogenic roles. To address this issue, human T cells were transduced with the constitutively active STAT3 mutant STAT3C. Following stimulation, STAT3C + T cells up‐regulated IL‐10 (4.1 ± 0.5‐fold; P < 0.001) and granzyme B (2.5 ± 1.2, P < 0.05) secretion, combined with significantly reduced IFN‐γ (35 ± 5%), IL‐2 (57 ± 4%), TNF‐α (64 ± 8%), and IL‐13 (89 ± 3%) secretion ( P < 0.001). CD3/CD2‐or CD3/CD28‐activated STAT3C + T cells revealed reduced proliferation (53.4 ± 23.5% and 70.5 ± 10.4%, respectively), which was independent of IL‐10 production and significantly suppressed effector T cell proliferation by 68.7 ± 10.6% and 65.9 ± 2.6%, respectively ( P < 0.001). Phenotypically, STAT3C ‐transgenic CD4 + T cells resembled effector T cells regarding expression of T regulatory cell markers, but up‐regulated granzyme B expression levels by 2.4‐fold ( P < 0.05). Suppression was cell contact dependent and mediated by granzyme B‐induced cell death, but was independent of IL‐10 and TGF‐β. Notably, peripheral blood CD4 + CD45RA – lymphocyte activation gene‐3 + CD49 + type 1 regulatory T cells revealed activation‐induced hyperphosphorylation of STAT3. In agreement, pharmacological inhibition of STAT3 activation partially reverted hyporesponsiveness of peripheral type 1 regulatory T cells (increasing their division index from 0.46 ± 0.11 to 0.89 ± 0.04; P < 0.01). These observations indicate a clear‐cut relation between activation of STAT3 and the acquisition of a tolerogenic program, which is also used by peripheral blood type 1 regulatory T cells.—Schmetterer, K. G., Neunkirchner, A., Wojta‐Stremayr, D., Leitner, J., Steinberger, P., Pickl, W. F., STAT3 governs hyporesponsiveness and granzyme dependent suppressive capacity in human CD4+ T cells. FASEB J. 29, 759–771 (2015). www.fasebj.org